Linked labor force trajectories: Empirical evidence from dual-parent families in the United States and Australia. (December 2022) - Mooi-Reci, Irma; Liao, Tim F.; Curry, Matthew
Abstract: To what extent are parents' and children's labor force trajectories associated and what factors shape these intergenerational labor force trajectories? We address these questions by proposing a linked labor force trajectory approach that compares monthly labor market attachment sequences over a 2.5 year period, first for parents, and for their children 12 years later when they reach young adulthood in their 20 s. Using triadic sequences from the U.S. Panel Study of Income Dynamics (PSID) ( N  = 488) and the Household, Income and Labour Dynamics in Australia (HILDA) Survey ( N  = 693), we show that children's labor force trajectories in young adulthood are strongly associated with the labor force trajectories of their parents. Intergenerational associations of labor force trajectory are strongest in "Job-rich" households where at least one parent is employed and weaker in "Job-poor" households, particularly in Australia. Low educational attainment, low maternal education (in Australia) and low paternal education (in the U.S.), family size, and family structure (in the U.S.), are among the most consistent factors generating associative patterns of "Job-poor" labor force trajectories between parents and children. Our findings suggest that parents' joint workforce engagement improves children's future labor force outcomes.